Sajadah Furqaan (SF) / Noorzalyla Mokhtar … [et al.] - Mokhtar, Noorzalyla; Mohamad Isa, Nur Hani Najihah; Mohd Hashim, Nur Roselinda Lily; Abd Majid, Farra Adlena; Ebrahim, Zarina Begum; Sauid, Muna Kameelah; Mustakim, Nurul Ain; Othman, Yuhanza (Division of Research and Industry Linkages, 2017)
Sajadah Furqaan or SF is suitable for all age. It comes in small and large size to accommodate kids and adults. This is a 2 in 1 product which is the combination of small carrier that functions as a table that made it easy for user to use it to read Quran after prayer. Besides, the table have the functionality to emit adzan sound and display adzan time (Imsak, Subuh, Syuruk, Dhuha, Zuhur, Asar, Maghrib and Isya’) and it also can count the number of sujud. This added functions of sujud’s counting is to help user to become aware of which rak'ah are they at; especially for older people. The sajadah uses velvet material and it can be separated from the carrier for the cleaning or traveling purpose. The usage of box made it easy to carry anywhere because it is light in weight and also convenient for storage. Method of using this product is put the carrier on the floor and then pulls the Sejadah out. To turn on the sound and prayer time, we need to put battery and set the time of adzan. For the sujud counting, the sajadah are equipped with sensor on it to detect number of sujud. If we put our forehead on the sajadah, it can count the number of sujud that we have done, so that people will not forget they are in what rakat (rak'ah). This product is ergonomic because it can ease the consumer and the product is also different from the ready made sajadah